Analisis Penerapan Tax Planning Atas Pajak Penghasilan Badan Pada CV. Ethanas Nusa Palapa - Salsabila Indranifia (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine the application of tax planning (tax planning) can affect the corporate income tax that will be paid by CV. Ethanas Nusa Palapa. This type of research uses descriptive qualitative research. Data collection techniques used are observation, documentation, and interviews. This study uses primary data and secondary data. The results of this study indicate that, CV. Ethanas has not done optimal tax planning. By implementing tax planning CV. Ethanas Nusa Palapa was able to reduce its tax obligations from Rp. 23,365,281 to Rp. 19,175,491 and saved Rp. 4,189,790 in taxes.